Contribution of Cash Management practices on Performance of Ankole Farmers Savings and Credit Cooperative Organization Rubindi Branch-Mbarara District. - Akankwasa, Alex; Akakikunda, Teddy; Ntirandekura, Moses; Masiko, Caroline Murezi; Nyesigire, Jolly (Kabale University, 2024)
This research carried out was about the Cash Management and Performance of Ankole Farmers Savings and Credit Cooperative Organization Rubindi Branch. The objectives of the research included: analyzing the factors affecting cash Management in Rubindi Savings and Credit Cooperative Organization, examining the challenges facing the organization, and finding out the effect of cash management on the financial performance of SACCO. The study used questionnaires and interviews as the methods for data collection. The study also established that cash management practices increase the flexibility and competitive advantage of an Organization, enabling it to take cash discounts. The findings showed that Cash management practices help SACCO to survive in uncertain environments and also influence forecasting the financial performance of these organizations. The managers of Savings and Credit Cooperative Organizations need to introduce better policies about cash management practices with the aim of boosting their liquidity and sustainability. The study recommended; introducing cash ratios, increasing deposits, recruitment of competent staff, maintaining liquidity and adopting a capital structure policy with the aim of facilitating decision-making and overall performance of the Savings and Credit Cooperative Organizations. The employees can facilitate further training in customer care management, loan appraisal, monitoring and assessment, and also financial management to assist the Savings and Credit Cooperative Organizations in realizing their goals and objectives.